Serious infections in children presenting at the emergency ward in Flanders (Belgium): The diagnostic value of demographic and clinical signs - Van Den Bruel, A; Raes, M; Aertgeerts, B; Buntinx, F (2007)
Readily available demographic or clinical variables could be helpful in identifying children at higher risk of suffering a serious infection. We analysed for the first time in Flanders (Belgium) the data of 384 children at an emergency ward. Serious infections were defined as sepsis, pneumonia, meningitis, urinary tract infection, bacterial gastroenteritis, bronchiolitis and cellulitis. The clinical and demographic variables were registered prospectively. A multivariate analysis was performed using logistic regression analysis. The prevalence of a serious infection was 25%. The probability of a serious infection was highest for children under the age of one. The odds ratio for children 1-3 years was 0.34 (95% CI: 0.17-0.71), for 4-6 years 0.18 (95% CI: 0.07-0.45) and for 7-16 years 0.36 (0.15-0.87). Children referred to the emergency ward by another doctor had an odds ratio of 2.2 (95% CI: 1.1-4.1) for having a serious infection, compared to self-referred children. When the attending ward physician judged the child to be fairly or seriously ill at first impression, the odds ratio for a serious infection amounted to 3.8 (95% CI: 2.0-7.4) and to 11.7 (95% CI: 4.1-33.1) respectively. Age, referral and first impression of the attending ward physician are important criteria for identifying children at higher risk of having a serious infection in the emergency ward.